Impacts of Climate Change on Land Degradation: A Review of Mitigation - C D N Sinha (International Journal of Land, 2025)
Land degradation has emerged as one of the most pressing environmental challenges globally, significantly impacted by the multifaceted and escalating effects of climate change. The degradation of land, including soil erosion, nutrient depletion, deforestation, and desertification, directly threatens food security, biodiversity, and human livelihoods. As climate change leads to increasingly erratic weather patterns, including prolonged droughts, intense rainfall, and extreme temperatures, land degradation has become more pronounced and widespread, exacerbating existing vulnerabilities. This review examines the complex relationship between climate change and land degradation, detailing how changes in climatic conditions exacerbate the rate and severity of land degradation across various ecosystems. The paper highlights the role of both natural and anthropogenic factors, such as unsustainable agricultural practices, deforestation, and urbanization, in compounding land degradation.Additionally, the review delves into a comprehensive range of mitigation and adaptation strategies aimed at counteracting the adverse effects of climate change on land quality. Mitigation strategies, such as the promotion of sustainable agriculture, soil conservation techniques, and reforestation, have shown promise in restoring degraded lands, improving soil health, and enhancing ecosystem resilience. Adaptation strategies, including climate-smart land management (CSLM) practices, land restoration initiatives, and community-based approaches, are also pivotal in fostering long-term land health and resilience. The review further explores the importance of collaborative efforts between governments, local communities, and international organizations to implement effective policies and practices that mitigate land degradation while also adapting to its impacts. By integrating scientific advancements, traditional knowledge, and policy frameworks, this review provides valuable insights into the pathways toward sustainable land management and the future resilience of ecosystems and human societies
Keywords: Climate change; Land degradation; Mitigation strategies; adaptation strategies; soil conservation; sustainable land management